Legal Counseling to Increase Public Legal Awareness of Citizen Rights and Obligations - Bambang Irawan; Indah Susilowati; Irman Putra; Arief Fahmi Lubis; Dian Kemala Dewi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
The law education program implemented in Cempaka Putih Subdistrict, East Jakarta, aims to increase legal awareness among the community, particularly those aged 23-60 who do not have a permanent job. This program uses interactive presentation methods and participatory discussion to facilitate a deeper understanding of citizens' rights and obligations. The results of the program's implementation show a significant increase in participants' understanding of law, as reflected in a survey that shows a surge in awareness and ability to resolve legal conflicts peacefully. The program also successfully increased community participation and built a stronger legal support network among participants. The positive response from the community and requests for further programs demonstrate the program's success and relevance in empowering the community. Through a suitable approach, this law education program has had a positive impact, reducing minor legal issues, and promoting active participation in social and economic activities. Therefore, the development of additional materials is necessary to further explore more specific legal issues, ensuring the continuation of the program's benefits for the community of Cempaka Putih Subdistrict